Pengujian Performa Prototype Mesin CNC Miiling 3 Axis Dari Limbah Elektronik - Alvi Syahri; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
CNC machines (Computer Numerically Controlled) are machines that are controlled by CNC machines computers using numerical instructions (command data with code numbers, letters and symbols). CNC work system technology is a combination of computer and mechanics, so that when compared with similar machine tools, CNC Milling machine tools can be rigorous, more precise, more flexible and suitable for mass production. capable tools Currently CNC machines are increasingly being made or developed either CNC machines in large scale dimensions or in prototypes. Assembling 3 Axis CNC Milling Machine prototypes, namely X, Y and Z axis. The purpose of the research is to find out the important components and how to operate them, the level of precision, the accuracy and the area of the work area of the machine. The 3 axis CNC Milling prototype machine has dimensions of engine length X 40 mm, Y 38 mm and Z 16 mm. The 3 Axis CNC Milling prototype machine has the advantage of being able to create images which are then forwarded to the 3 Axis CNC Milling machine in the production process. The test results obtained an accuracy value of 0.5 mm, the value of the precission of the X axis line pattern was 0.087 mm, the Y axis was 0.099 mm, and the diameter of the circle pattern was 0.064 mm.Key Words : CNC Milling 3Axis prototype, Work Area, accuracy, precission